Impact of solvent type, solvent-water concentration, and number of stages on the extraction of coumarin mixture from tamanu (Calophyllum inophyllum) oil and its antioxidant activity - Safrina Hapsari; Nurul Jadid; Hakun Wirawasista Aparamarta; Setiyo Gunawan (Arabian Journal of Chemistry, 2023)
Natural products have been receiving the spotlight from the people of developing and developed countries in recent years due to rising health care expenses and global financial crises. These natural products are the resources for bioactive compounds used in the drug development process. Tamanu seed oil is used for traditional remedies and cosmetic ingredients. The dried seed produces an oil with a yield of 50–75 %. Previous works reported that the seed oil comprised coumarins, one of the eminent groups of phenolics. Coumarins have anticancer, antimicrobial, anti-inflammatory, anticoagulant, antiviral, wound healing properties, and anti-HIV effects. Extraction is often referred to as the sample preparation method as its essential to purify bioactive compounds. In this work, coumarin mixture from tamanu oil was extracted by batchwise multi stages extraction. The effects of solvent used (methanol and ethanol), solvent–water concentration, and the number of stages were studied. The optimal conditions for the extraction of the coumarin mixture were 90 % ethanol and eight stages of extraction, which contributed to 50.73 ± 0.16 % of purity and 92.95 ± 3.76 % of recovery. Also, these conditions removed up to 66 % free fatty acids (FFA) and 100 % triglycerides (TG). It was found that the DPPH inhibition at 400 ppm shows that 90 % ethanol has the highest inhibition (57.72 ± 2.70 %) with an IC50 value of 305 ppm. Moreover, various compounds like pyrrole-2 carboxylate, epicrinamidine, cholestane, and hydroxysclerodin trimethyl ether were also detected in the polar fraction of tamanu oil.